1994
DOI: 10.1007/bf00326580
|View full text |Cite
|
Sign up to set email alerts
|

Genetic requirements for initiating asexual development in Aspergillus nidulans

Abstract: Conidiation in the filamentous ascomycete Aspergillus nidulans requires activation of brlA, a well-characterized transcriptional regulator of genes that are induced specifically during asexual development. We have isolated and characterized developmental mutations in six loci, designated fluG, flbA, flbB, flbC, flbD, and flbE, that result in defective development and reduced brlA expression. These mutants grow indeterminately to produce masses of aerial hyphae resulting in the formation of cotton-like colonies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
189
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 24 publications
4
189
0
1
Order By: Relevance
“…The results obtained in this work lead us to propose that KapI is not the importer of FlbB. In addition, as brlA is expressed in the null DkapI background but not in flbD null (Wieser & Adams, 1995) or flbC mutants (Wieser et al, 1994), we discard the possibility of an exclusive import of those two TFs by KapI.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The results obtained in this work lead us to propose that KapI is not the importer of FlbB. In addition, as brlA is expressed in the null DkapI background but not in flbD null (Wieser & Adams, 1995) or flbC mutants (Wieser et al, 1994), we discard the possibility of an exclusive import of those two TFs by KapI.…”
Section: Discussionmentioning
confidence: 65%
“…(G g ) and at the periphery of the colony (G p ), and specific growth rate (m) of wild-type and DkapI strains All parameters were calculated as described in Methods and are means±SEM of multiple measurements as described in Results. brlA is expressed in the absence of KapI activity UDA factors are positively required for brlA transcription (see Introduction) and some of the mutants in this regulatory pathway are called flb due to the fluffy phenotype associated with a low brlA expression level (Wieser et al, 1994). In contrast to DflbB (Etxebeste et al, 2008), or to other flb mutants such as DflbE , we detected brlA transcription in the DkapI deletion strain (Fig.…”
Section: Flbb Nuclear Import Does Not Require Kapimentioning
confidence: 81%
“…Further studies by Kale et al (60,61) revealed that these A. flavus and A. parasiticus developmental mutants also lack aflR and aflatoxin enzymatic gene transcripts and fail to accumulate other aflatoxin pathway intermediates. A similar phenotype was found in developmental A. nidulans mutants called "fluffy" (37,78,117,123). Hicks et al (55) demonstrated that some of these A. nidulans developmental mutants are also deficient in sterigmatocystin production.…”
Section: Signal Transduction Pathwaymentioning
confidence: 59%
“…From these examples it is clear that the G-protein signaling pathway is essential for fungal growth and infection. (4,5,37,70,123). Two of these genes, fluG and flbA, were later found to regulate both asexual development and sterigmatocystin production (55), with fluG believed to act upstream of flbA (Fig.…”
Section: Overview Of Signal Transduction In Fungimentioning
confidence: 99%
“…The genes fluG and flbA-C encode developmental regulators that act upstream of brlA, and their deletion reduces the expression of brlA, resulting in aconidial, fluffy phenotypes (Adams et al 1992(Adams et al , 1998Wieser et al 1994). Thus, our next question was whether these regulatory genes were also induced by light.…”
Section: Identification Of Light-regulated Conidiation Genes In a Nimentioning
confidence: 99%